Key challenges faced by main contractors in coordinating the works of their subcontractors: a case study of Kusile power station project - Noganta, Abongile (My University, 2019)
Coordination is a crucial function in the management process of interdependent parties and their activities. In major construction projects, where there are manifold participants; the contractor is faced with the challenge of coordinating the interdependent subcontractors’ tasks and subtasks in ensuring that quality standards, time and cost requirements are met and ultimately project success is achieved. Lack of coordination of subcontractors’ works by the main contractors is one of the causes of deviations from project goals such as delivering a quality project within time and cost. This research is directed at identifying the key challenges that main contractors face when coordinating the subcontractors’ works in major construction projects and how they overcome these challenges. Kusile Power Station was chosen as a case study for this research because it is a large project whereby the problem was observed by the researcher. This case was strategically selected because of the numerous contractors (at different levels) working at the peak stage of the project. In-depth interviews were held with four main contractors’ representatives dealing with coordination at the Kusile Power Station Project. These four main contractors were selected based on the scope they are contracted to do, size of the company, and the number of subcontractors they manage and were responsible for. The four main contractors interviewed had 46, 8, 9 and 6 subcontractors respectively. 32 challenges were identified and grouped into 7 seven distinct groups. The key conclusions from the research data analysis was that resource handling (issues), clashes/ changes in designs/ drawings, and access issues are the three key coordination challenges faced by main contractors at the Kusile Power Station Project. To overcome these major challenges, the contractors perform & make use of resource scheduling, two/ three week look ahead, and site walks. It is recommended that a similar study he done in another major project to uncover other means of dealing specifically, with the three key challenges